2019
DOI: 10.1016/j.bios.2019.111334
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible propulsion for biomedical micro/nano robotics

Abstract: Micro/Nano robots have shown enormous potential for diverse biomedical applications, such as targeted delivery, in vivo biosensing, minimally invasive surgery and cell manipulation through extending their area of operation to various previously inaccessible locations. The motion of these small-scale robots can be either self-propelled or remotely controlled by some external power sources. However, in order to use them for biomedical applications, optimization of biocompatible propulsion and precise controllabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 136 publications
0
50
0
1
Order By: Relevance
“…Although light is generally considered to be an actuator suitable for biological applications, [ 184 ] a thorough biocompatibility study is necessary for each individual optical control configuration, as specific combinations of wavelength and power can have different effects on cells, tissues, or bodily fluids. Typically, nIR light is considered safe for biological entities, provided that the power used is not too high, as it is the case for optical trapping setups.…”
Section: Challenges In the Fabrication And Optical Actuation Of Polymeric Microrobotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although light is generally considered to be an actuator suitable for biological applications, [ 184 ] a thorough biocompatibility study is necessary for each individual optical control configuration, as specific combinations of wavelength and power can have different effects on cells, tissues, or bodily fluids. Typically, nIR light is considered safe for biological entities, provided that the power used is not too high, as it is the case for optical trapping setups.…”
Section: Challenges In the Fabrication And Optical Actuation Of Polymeric Microrobotsmentioning
confidence: 99%
“…A recent study showed that to reduce potential inflammatory responses, the microrobot design should minimize any physical interactions with the cells of the immune system while improving the locomotion performance of the microrobots. [183] Although light is generally considered to be an actuator suitable for biological applications, [184] a thorough biocompatibility study is necessary for each individual optical control configuration, as specific combinations of wavelength and power can have different effects on cells, tissues, or bodily fluids. Typically, nIR light is considered safe for biological entities, provided that the power used is not too high, as it is the case for optical trapping setups.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Similarly, bubble‐mediated propulsion of nano‐ and micromotors, as discussed in the previous section, may be advantageous in tissue deconstruction as well. [ 187–189 ] Kagan et al demonstrated PFC‐loaded microbullets capable of tissue penetration, as well as inducing tissue expansion and splicing under acoustic droplet vaporization (Figure 9C). [ 187 ] The incorporation of photothermal agents in PFC droplets allows for optical droplet vaporization by laser light, which could be advantageous for photoacoustic imaging.…”
Section: Modification Of the Surrounding Environmentmentioning
confidence: 99%
“…The mimicking of natural motility behaviour using synthetic soft materials has been discussed by Samuel Sanchez et al 26 The biocompatibility of propulsion techniques has been discussed by Halder and Sun. 27 Several reviews towards biomedical applications have also been published. In 2018, Guan et al discussed the use of micro/nanorobots for active drug delivery.…”
Section: Introductionmentioning
confidence: 99%